2014
DOI: 10.1175/jcli-d-14-00033.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Controls on the Persistence of La Niña*

Abstract: A large fraction (35%-50%) of observed La Niña events last two years or longer, in contrast to the great majority of El Niño events, which last one year. Here, the authors explore the nonlinear processes responsible for the multiyear persistence of La Niña in the Community Climate System Model, version 4 (CCSM4), a coupled climate model that simulates the asymmetric duration of La Niña and El Niño events realistically. The authors develop a nonlinear delayed-oscillator (NDO) model of the El Niño-Southern Oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 58 publications
5
65
0
Order By: Relevance
“…Different hypotheses have been proposed to explain the decadal/multi-decadal anomalies in the tropical Pacific202324252634353637383940414243. It has been argued that the El Niño-La Niña asymmetry may contribute to the decadal background change in the tropical Pacific25353637.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different hypotheses have been proposed to explain the decadal/multi-decadal anomalies in the tropical Pacific202324252634353637383940414243. It has been argued that the El Niño-La Niña asymmetry may contribute to the decadal background change in the tropical Pacific25353637.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…While the strong positive skewness in the eastern Pacific implies that warm decadal anomalies there may be partly ascribed to the EP El Niño itself, the weak negative skewness in the central Pacific indicates that decadal anomalies there are less influenced by the El Niño-La Niña asymmetry. It has also been argued that multi-year persisting La Niña anomalies induced by nonlinear processes and the rectification of El Niño-Southern Oscillation (ENSO) events may contribute to the Pacific decadal/multi-decadal anomalies3839. Previous studies have also suggested the important roles of internal ocean-atmosphere processes in generating the Pacific ENSO-like decadal/multi-decadal variations23244041.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is generally accepted that there is an asymmetry in the duration of the two phases of ENSO events, with La Niña events lasting longer than El Niño events (Larkin and Harrison 2002;McPhaden and Zhang 2009;Obha and Ueda 2009;Okumura and Deser 2010;Okumura et al 2011;DiNezio and Deser 2014). Given that McGregor et al (2013) proposed that the asymmetries in the southward wind shift (e.g., El Niño event magnitude is strongly related to the extent of the meridional wind movement, while the meridional wind movement during La Niña events remains relatively small The boxplots in Fig.…”
Section: Duration Asymmetrymentioning
confidence: 99%
“…Many La Niña events persist through their second year and sometimes reemerge in the subsequent winter (e.g., Ohba and Ueda 2009;Ohba et al 2010;DiNezio and Deser 2014;Hu et al 2014). For example, the 1998/99 La Niña event starts at about July 1998 and lasts for nearly three consequent years.…”
Section: B Definition Of Enso Eventsmentioning
confidence: 99%